2018
DOI: 10.1101/332197
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic control of proinflammatory cytokines Il-1β and Tnf-α by macrophages is necessary for functional spinal cord regeneration in zebrafish

Abstract: Spinal cord injury leads to a massive response of innate immune cells (microglia, macrophages, neutrophils) both, in non-regenerating mammals and in successfully regenerating zebrafish, but the role of these immune cells in functional spinal cord regeneration in zebrafish has not been addressed. Here we show that inhibiting inflammation reduces and promoting it accelerates axonal regeneration in larval zebrafish. Mutant analyses show that peripheral macrophages, but not neutrophils or microglia, are necessary … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…In addition macrophages are also shown to involve in the process of regeneration of heart/cardiomyocytes in different animals (Zebra fish, Salamander, and the laboratory mouse) [165][166][167]. Even studies have also shown the involvement of macrophages in the regeneration of spinal cord and tail fin of Zebra fish [168,169]. Wnt signaling in macrophages plays a critical role in driving parenchymal regeneration in animal models of liver injury [170].…”
Section: Macrophages In Regenerationmentioning
confidence: 99%
“…In addition macrophages are also shown to involve in the process of regeneration of heart/cardiomyocytes in different animals (Zebra fish, Salamander, and the laboratory mouse) [165][166][167]. Even studies have also shown the involvement of macrophages in the regeneration of spinal cord and tail fin of Zebra fish [168,169]. Wnt signaling in macrophages plays a critical role in driving parenchymal regeneration in animal models of liver injury [170].…”
Section: Macrophages In Regenerationmentioning
confidence: 99%
“…Macrophages are also critical for regeneration of fin, retina, and heart in zebrafish (Huang et al, 2012; Petrie et al, 2014; Sanz-Morejon et al, 2019). In contrast, several studies showed that microglia are not necessary for murine axonal regeneration (Hilla et al, 2017) and spinal cord repair in zebrafish (T. M. Tsarouchas et al, 2018). Though many studies have shown that the microglial response after injury, whether microglia are required for successful repair after acute brain injury in zebrafish is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, acute inflammation appears necessary for promoting regeneration after injury in zebrafish. Inflammatory mediators implicated in the zebrafish CNS pro-regenerative response include leukotrienes in brain (Kyritsis et al, 2012), interleukin (il) 6, il11, and leptin in retina (Wan et al, 2014; Zhao et al, 2014), and tnf α and Il1 β in spinal cord (T. M. Tsarouchas et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in amoeboid profiles that occurs between 4 h and 12 h after cautery deafferentation may be due to a delayed recruitment phase. A recent study reported anti-inflammatory cytokines, such as tgf-β1a and tgf-β3, being expressed at low levels during initial regeneration, and upregulated during late regeneration in zebrafish, suggesting a biphasic immune response within the 48 h after injury (Tsarouchas et al, 2018). Other studies have suggested that adult microglia have a low proliferation level and slow turn-over rate in mice (McCarthy and Leblond, 1988; Lawson et al, 1992; Inman and Downs, 2007), suggesting proliferation and reconstitution of microglia to be the limiting factor, perhaps exacerbated by the severity of the damage.…”
Section: Discussionmentioning
confidence: 99%
“…Sections were rinsed in PBS and placed in blocking solution (3% normal goat serum, 0.4% Triton X-100 in PBS) for 1 h at room temperature and in 4C4 mouse monoclonal antibody (1:100, a kind gift of Drs. Pamela Raymond and Peter Hitchcock, University of Michigan) to label microglia (Becker and Becker, 2001; Raymond et al, 2006; Craig et al, 2008; Baumgart et al, 2012; Tsarouchas et al, 2018). Sections were rinsed in PBS and then incubated in biotinylated goat anti-mouse secondary antibody (1:200, Vector Laboratories, Burlingame, CA, USA) for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%